1978
DOI: 10.1128/aem.35.5.906-910.1978
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacillus thuringiensis spores by ultraviolet and visible light

Abstract: The inactivation of Bacillus thuringiensis spores and spores treated with two protectants, one proteinaceous and the other a commercial product, Shade, at wavelengths of the near-ultraviolet and visible spectra and at 254 nm is described. Determination of the inactivating wavelengths may be used to establish an efficient sunlight protective system for B. thuringiensis when used as a microbial insecticide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 26 publications
3
38
0
9
Order By: Relevance
“…A further study of B. subtilis spores found that wavelengths in the range 410–570 nm also significantly affected the outgrowth of spores (31). Griego and Spence (29) investigated the effect of different wavelength ranges between 290 and 700 nm on B. thuringiensis spores and found that maximum inactivation was achieved with exposure to 400 nm light. An absorbance peak at 408–420 nm together with the inactivation activity in the region of 400 nm lead the authors to hypothesize that the light energy was being absorbed by a target molecule, producing a photoproduct that halted replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further study of B. subtilis spores found that wavelengths in the range 410–570 nm also significantly affected the outgrowth of spores (31). Griego and Spence (29) investigated the effect of different wavelength ranges between 290 and 700 nm on B. thuringiensis spores and found that maximum inactivation was achieved with exposure to 400 nm light. An absorbance peak at 408–420 nm together with the inactivation activity in the region of 400 nm lead the authors to hypothesize that the light energy was being absorbed by a target molecule, producing a photoproduct that halted replication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies into the visible/blue light inactivation of various bacterial species have indicated that porphyrins are the endogenous photosensitive molecules involved in this process (13–17). Bacillus species have been documented to contain endogenous porphyrin molecules (41), and the absorption peak of 408–420 nm reported for B. thuringiensis spores (29) correlates well with the large porphyrin absorption peak at 400–420 nm (termed the “Soret band”; 42), therefore it is likely that porphyrin molecules are also the photosensitive molecules involved in spore inactivation. Heme proteins, members of the porphyrin family, have been suggested to have an involvement in the spore inactivation process, with the more resilient nature of the spores even being proposed to be due to the reduced level of these molecules found in spores compared with vegetative cells (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential endophytic nature of B. thuringiensis, which might be improved artificially, may become an alternative pest control strategy, similar to Bt crops, where toxic crystals are protected from the sunlight as well as from leaching by the rain (Griego and Spence 1978;Behle et al 1997;Ruan et al 2004;Raymond et al 2010). For this reason, we tested the ability of the sporecrystal complex of B. thuringiensis to translocate from the root to the upper parts of the plant, keeping its viability and, most importantly, its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Maclean also verified that their high‐intensity light technique does not encourage endospore germination. The efficacy of this 405 nm therapy may be explained by the presence of endogenous porphyrins such as coproporphyrin with Soret bands in the 400–420 nm regions of the visible spectrum in Bacillus and Clostridium bacteria . Thus, the sporicidal effect of blue light is probably an oxygen‐dependent process akin to the light‐mediated destruction of Helicobacter pylori and Propionobacterium acnes —a photodynamic inactivation relying on pathogen's biosynthesis of endogenous photosensitizers .…”
Section: Introductionmentioning
confidence: 99%